Evaluation of Discharge Calculation in Open Pit Mining - Ivan Kurniawan; Satria Damarnegara; Nastasia Festy Margini (Institut Teknologi Sepuluh Nopember (ITS), 2023)
This study presents the discharge calculation of open pit mining drainage system in open pit mine at PT Maruwai Coal, in Central Kalimantan. Several calculation methods are compared, including FJ Mock, HEC-HMS, and 2D HEC-RAS simulation. The open pit mine drainage system consists of sump storage with volume of 12.574 m3 and discharged using 0,22 m3/s pump. The loss method for HEC-HMS and HEC-RAS is modelled using Curve Number (CN) approach. CN value choice need to consider steep slope condition at the site. Storage elevation and pump operation at 10 rainfall event is observed and used as model validation. The calculation shows each method is capable to model the event reasonably well. The average run-off coefficient varies from 0.72 for FJ Mock and 0.63 for HEC HMS. However, FJ Mock method gives daily average value and may underestimate the run-off discharge. Indeed, HEC-HMS and HEC-RAS model is more suitable for flood modelling because of unsteady nature of the flow.